PERILAKU KECANDUAN MENONTON DRAMA KOREA DAN SELF CONTROL (KONTROL DIRI) SISWA SMAN 7 PEKANBARU - Riska Oktadianti; Tri Umari; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: The current phenomenon of addiction to watching Korean drama has an impact on self-control (student self control), such as students being forgetful of time when watching, not focusing on learning, getting nervous when not watching. Therefore, researchers feel interested to conduct research entitled Behavior Addicted Watchhing Korean Drama and Self Control (student control) students. This study aims to determine; 1) An image of addiction behaviorwatching Korean drama; 2) Description of self-control (self control) students in SMAN 7 Pekanbaru. The method of this study was descriptive with the subjects of study of addicted students watching Korean dramas with high categories who watched <6 episodesand found 22 students as subjects. Data collection techniques in the form of questionnaires and data analysis technique technique percentage. The result of this study; 1) Students always feel dissatisfied just watching 2 episodes of Korean drama, students often spend a lot of time watching Korean drama than any other activity, students always get carried away after watching Korean drama, students always spend the day watching Korean dramas, students always have spare drama to be watched, students always goback to watch despite long stops; 2) Self control students who are addicted to watching Korean dramas that students do not force themselves to watch when sick, according to Korean drama student are not contrary to his belief, students always think before acting and students always finish the task before piling up. The conclusion of this study is the behaviour of addiction watching Korean dramas are in the moderate category with self control in the medium category. Suggestions for future researchers are expected to conduct further research from several schools in order to collect complete data.Key Word: Addiction, Korean Drama, Self Control